'Hyper-gender' asymmetries: women's absence in illegal taking from nature (Poaching) (Notes from Bulgaria and Murmansk Region, NW Russia). (3rd July 2018) - Konstantinov, Yulian
ABSTRACT: The paper addresses a little examined case of gender asymmetry: the absence of women in game poaching. Observations of the phenomenon in rural Bulgaria and the reindeer-husbandry part of Murmansk Region indicate a type of boundary between legal and illegal game hunting that is rarely crossed by women and thus suggests presence of a 'hyper-gender' asymmetry. By the latter, I mean an excessively pronounced absence of women, compared to other situations in which men predominate. The radicalism of this divide and the nature of its construction and continuation weakens the thesis in 'culture/nature' debate regarding binaries as the work of empowered subjecthood in a teleology of domination. Using the case study of illegal taking from nature to explore the concept of hyper-gender asymmetry, I argue, instead, for the possibility of binary constructivism realized at a grassroots actors' level, i.e. 'from below.'